EKSPRESI BUDAYA TUTUR MASYARAKAT MADURA DALAM TRADISI PERNIKAHAN (KAJIAN FENOMENOLOGI) - Sulistiyono Sulistiyono (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
Language and culture are two things that are difficult to separate where cultural studies present the study of language automatically. Madurese is a unique language with three levels of language, namely rough (enja’-iya), medium (enggi-enten) and fine (enggi-bunten). The Madurese language is increasingly less desirable and needs preservation which can be developed in various forms such as implementation in learning, habituation or with cultural preservation such as the Mantu tradition. The purpose of this study is to describe the use of Madurese speech language with a good and correct level of speech in the mantu tradition event. The speech used in the Mantu tradition uses good word selection by paying attention to the speaker's situation and the aesthetics of the speech. The aesthetics of the language are then supported by the use of Saloka, proverbs and Pantun. In general, the greeting framework for the in-laws tradition is the opening greeting, preamble, greeting words, thanks, the content of the speech consisting of the beginning, middle and end before then ending with the closing section and closing greetings.